The Prover and the Source - Schlingensiepen-Brysch, Irene; Dattler, Andra (Homœopathic Links, 2012)
The Source‐Method of homeopathic prescribing, as developed by Irene draws on the observation that every patient seems to have an intrinsic knowledge about the Source, from which his/her simillimum remedy can be produced. The Source‐Method of case‐taking relies strictly on the patientʼs own words and narrative as a reliable guide to the Source, avoiding any interpretation or “intuition” by the homeopath. This article describes an experiment to reverse this approach in the setting of a homeopathic proving. The question was: does a prover develop a similar, subconscious “knowledge” about the proving substance? Can this knowledge be accessed in a double blind setting? The most notable observations in this experiment were the striking clues to the Source in the seemingly senseless portions of the interview. They indicate that a homeopathic proving can produce subconscious images similar to the way patients describe their unique Source.
Keywords: information coming from the source; A homeopathic proving; Source-Method